Functional characterization of dark sleeper (Odontobutis obscura) IRF3 in IFN regulation. Issue 89 (June 2019) - Li, Zhuocong; Chen, Jian; Li, Pei; Li, Xi-yin; Lu, Longfeng; Li, Shun
Abstract: The dark sleeper, Odontobutis obscura ( O. obscura ), is a commercially important species of freshwater sleeper native to East Asia. However, its molecular biology system is unexplored, including the interferon (IFN) signaling pathway, which is crucial to the antiviral response. In this study, we characterised the IFN regulation pattern of dark sleeper interferon regulatory factor 3 (OdIRF3), supplementing evidence of the conservation of this classical pathway in fish. First, the open reading frame (ORF) of OdIRF3 was cloned from the liver tissue by Rapid amplification of cDNA ends (RACE). Amino acid sequence analysis suggested that OdIRF3 is homologous with other fish IRF3 and that the N-terminal DNA-binding domain (DBD) and the C-terminal IRF-association domain (IAD) are conserved. Then, the cellular distribution demonstrated that OdIRF3 is located in the cytoplasm region and transfers into the nuclear region under stimulation. For the function identification, OdIRF3 activated several types of IFN promoters and induced downstream interferon stimulated genes (ISGs) expression. Finally, the overexpression of OdIRF3 significantly decreased viral proliferation. Taken together, these data systematically characterised the sequence, cellular location, and function in IFN expression of OdIRF3, shedding light on the molecular biology mechanism of the dark sleeper. Highlights: OdIRF3 promotes fish IFNs and ISGs' transcription. OdIRF3 locates at cytoplasm region and transfers into nuclear region by stimulation. Overexpression of OdIRF3 suppresses SVCV replication.